The Implementation of Fingerprint Absence and Online Absence in Improving Work Discipline - Ferdye, Muhammad Amin; Supriaddin, Nofal; Putera, Asrip (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research aims to find out the level of employee work discipline based on the fingerprint attendance system and online attendance system, as well as to find out the factors that strengthen employee work discipline in the fingerprint attendance system and online attendance system. This research is descriptive research with qualitative analysis methods, with an interactive model using the Miles & Huberman approach. The results of this research show that the fingerprint attendance system is good in terms of increasing employee time discipline and regulatory discipline because it has a good security system. However, this attendance system has not had a positive impact on increasing responsible discipline. The results of research on the online attendance system are that the online attendance system is good in terms of increasing responsible discipline, because the online attendance system is integrated with daily performance reports, thereby increasing employee motivation at work. On the other hand, online attendance still needs to be developed to improve time discipline. The weakness of this system is that it also has a wide coordinate point for absences, making it possible for employees to be absent even when they are outside the office.